Сonsistent analysis of criterion parameters informativeness signals - Юдін, О.К. (Proceedings of National Aviation University (archive), 2006)
The goal of this article is synthesis of algorithm's consistent criterion of making a decision on the concept basis of adequate information. The considered method carries out of making a decision consistently with information accounting, which were saved on previous intervals of supervision, that enables its uses for a wide range of tasks of automated management.